Komunitas yang Dikasihi sebagai Obat Rasisme: Membedah Teologi Publik Martin Luther King, Jr. - Frederick Ray Popo; Barry Ekaputra; Wahyu Santoso (Fidei: Jurnal Teologi Sistematika dan Praktika, 2026)
Racism remains a persistent social problem, rendering the thought and praxis of Martin Luther King, Jr. continually relevant. This article examines King’s role as a public theologian in his struggle against racial discrimination in the United States, particularly within the context of systemic oppression institutionalized through Jim Crow laws. Employing a literature-based research method, this study analyzes King’s sermons, speeches, writings, and relevant secondary sources. The findings indicate that King’s public theology is grounded in biblical inspiration and an ethical understanding of agape love, which is embodied in a strategy of nonviolent resistance. On this foundation, King articulated the vision of the beloved community, a social order characterized by equality, justice, peace, and freedom. This article concludes that King’s thought possesses trans-contextual transformative potential and, through critical reflection, can be creatively appropriated within the Indonesian context to address various forms of discrimination and structural injustice. AbstrakRasisme merupakan persoalan sosial yang terus aktual, sehingga pemikiran dan praksis Martin Luther King, Jr. tetap relevan untuk dikaji. Artikel ini bertujuan menelaah peran King sebagai teolog publik dalam perjuangannya melawan diskriminasi rasial di Amerika Serikat, khususnya dalam konteks penindasan sistemik yang dilembagakan melalui peraturan Jim Crow. Penelitian ini menggunakan metode kajian pustaka dengan menganalisis khotbah, pidato, tulisan King, serta literatur sekunder yang relevan. Hasil kajian menunjukkan bahwa teologi publik King berakar pada inspirasi Kitab Suci dan pemaknaan etis atas cinta agape, yang diwujudkan melalui strategi perjuangan non-kekerasan. Dari landasan ini, King merumuskan visi the beloved community, yakni tatanan sosial yang ditandai oleh kesetaraan, keadilan, perdamaian, dan kebebasan. Artikel ini menyimpulkan bahwa gagasan King memiliki daya transformatif lintas konteks dan, melalui refleksi kritis, dapat diapropriasi secara kreatif dalam konteks Indonesia untuk menghadapi berbagai bentuk diskriminasi dan ketidakadilan struktural.